Rediscovering Teaching in University: A Scoping Review of Teacher Effectiveness in Higher Education - Mastrokoukou, Sofia; Kaliris, Andronikos; Donche, Vincent; Chauliac, Margot; Karagiannopoulou, Evangelia; Christodoulides, Pavlos; Longobardi, Claudio (Frontiers in Education, 2022)
Although teacher effectiveness plays a critical role in the learning process, little is known about its conceptualization and assessment, particularly in higher education (HE). This review aims to fill this gap by (a) listing the literature on teacher effectiveness, (b) identifying the instruments that have been used to assess teacher effectiveness (HE), and (c) highlighting the most effective teaching approaches based on the relevant literature. The selection process considered studies published since 1990 and conducted in higher education contexts with students. The research articles measured instructional processes and faculty effectiveness in terms of student outcomes, focusing on student achievement and student satisfaction. In reviewing the international research, special attention was paid to Southeastern Europe and Greece in particular. After a thorough review, the analysis revealed 26 studies. The results show that there is no universal definition of effective higher education teaching. Effective teaching may manifest itself in high scores on student performance assessments or in rewarding classroom interactions. Based on this principle, the way teacher effectiveness is defined is closely linked to proposed solutions in educational policy. Furthermore, research has shown that student-centered teaching styles are perceived by students as more effective, engaging, and performance-enhancing. However, several studies have not clarified why different teachers use different teaching styles in similar contexts. This review represents a step forward in our understanding of teacher effectiveness in HE. Nonetheless, effective teaching strategies could be better conceptualized through future research aimed at assessing the contextual nature of teaching along with student perceptions of effectiveness and expectations for an effective classroom climate.